ЄВРОПЕЙСЬКО-ПРАВОВИЙ ДОСВІД ЗАБЕЗПЕЧЕННЯ ЖИТТЄДІЯЛЬНОСТІ ВУГІЛЬНИХ МОНОМІСТ В УМОВАХ ЕНЕРГЕТИЧНОЇ ТРАНСФОРМАЦІЇ - Kirin, R.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
The article is devoted to the analysis of the features of ensuring the life of coal monofunctional cities in the conditions of energy transformation, which should be based not only on the legal definitions of the main categories, but also on the legal qualifications and the ratio of their object-subject compositions. It was determined that the Energy Strategy of Ukraine — 2035 focuses on the subject composition of certain types of transformation relations, while the object circle, after a complete rejection of coal in the energy sector and the termination of any subsidies to this sector, requires: coordination of structural changes with all stakeholders including the local population; basing plans for diversifying the economy, restructuring the coal industry, developing the infrastructure of post-coal regions on appropriate financial support, creating trust funds that will combine state, private and international assistance of various levels; transformation of unprofitable mines and, first of all, as an integral technically and organizationally separate (single) property complex of funds and resources. The concept of “coal monofunctional city” — a satellite of a city-forming enterprise for the extraction and processing of coal — an administrative-territorial unit, the specialization of labor of the population in which is determined by a set of directions for ensuring the operation of this enterprise and the life of its employees is proposed. The concept of “life activity of an employee of a coal mining enterprise is proposed — a set of daily processes, actions, activities that can ensure the existence of an employee, his family members, the entire workforce as a whole through training, communication, orientation, movement, self-service, control over his behavior, participation in labor activities with the help of physical, psychological and social functions”. It has been substantiated that the considered experience of such European coal-mining countries as Germany, Ro mania, Czech Republic, Poland, Great Britain can and should be adapted in the process of developing domestic con ceptual, strategic or program documents to support the life of coal monocities in the following blocks of relations: energy; environmental; social; economic; informational; administrative; housing and communal services; transport; law enfor cement. REFERENCES